2021
DOI: 10.2106/jbjs.cc.21.00159
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Dislocation of the Elbow in an Adult with Ehlers–Danlos Syndrome

Abstract: Case: A 32-year-old man with Ehlers–Danlos syndrome (EDS) fell while snowboarding and injured his right elbow. Radiography revealed a posterior dislocation of the elbow and a proximal radioulnar joint dislocation. A diagnosis of transverse divergent dislocation of the elbow was established. Open reduction and repair of the annular ligament, anterior oblique ligament, and capsule was performed with good clinical results. Conclusion: This is the first rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Each type in our study was demonstrated in previous literature [2][3][4][5][6]. These concomitant fracture-dislocations of the forearms further complicated the DDE in adults, which brought a considerable challenge to orthopaedic surgeons.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Each type in our study was demonstrated in previous literature [2][3][4][5][6]. These concomitant fracture-dislocations of the forearms further complicated the DDE in adults, which brought a considerable challenge to orthopaedic surgeons.…”
Section: Discussionsupporting
confidence: 58%
“…This evidence showed that the forearm was in a position of supination and the displaced humerus divorced the radius and ulna. Moreover, recent literature mentioned that annular ligament (AL) reconstruction should be considered due to a posterolateral dislocated radial head [6]. However, our surgeon did not find the AL damage due to the dislocated radial head during surgery.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation